Different therapeutic approaches in melasma: advances and limitations - Ghasemiyeh, Parisa; Fazlinejad, Rahil; Kiafar, Mohammad Reza; Rasekh, Shiva; Mokhtarzadegan, Mohammad; Mohammadi-Samani, Soliman (Frontiers in Pharmacology, 2024)
Melasma is a chronic hyperpigmentation skin disorder that is more common in the female gender.Although melasma is a multifactorial skin disorder, however, sun-exposure and genetic predisposition are considered as the main etiologic factors in melasma occurrence. Although numerous topical and systemic therapeutic agents and also non-pharmacologic procedural treatments have been considered in melasma management, however, the commonly available therapeutic options have several limitations including the lack of sufficient clinical effectiveness, risk of relapse, and high rate of unwanted adverse drug reactions. Recruitment of nanotechnology for topical drug delivery in melasma management can lead to enhanced skin penetration, targeted drug delivery to the site of action, longer deposition at the targeted area, and limit systemic absorption and therefore systemic availability and adverse drug reactions. In the current review, first of all, the etiology, pathophysiology, and severity classification of melasma have been considered. Then, various pharmacologic and procedural therapeutic options in melasma treatment have been discussed. Afterward, the usage of various types of nanoparticles for the purpose of topical drug delivery for melasma management was considered. In the end, numerous clinical studies and controlled clinical trials on the assessment of the effectiveness of these novel topical formulations in melasma management are summarized.